Donors' perspectives on self-deferral of men having sex with men from blood donation - Lee, Cheuk-Kwong; Lee, Krystal Chi-Kei; Lin, Che-Kit; Lee, Shui-Shan (Transfusion (Philadelphia, Pa.), 2013)
Background Self‐deferral of men having sex with men (MSM) from blood donation is a means of protecting blood safety. There has recently been a strategy change from permanent to time‐limited deferral in some countries. Awareness and attitudes of donors is crucial for effective implementation of MSM deferral or any change of the strategy. Study Design and Methods A postdonation survey was administered using a Web‐based questionnaire, after explanation by trained volunteers, to evaluate donors' awareness and compliance toward the health history enquiry (HHE, the deferral questionnaire) of the Hong Kong Red Cross Blood Transfusion Service, sexual experiences, and opinions on permanent versus time‐limited deferral. Results A total of 1373 Chinese donors (male:female 1.28:1), a majority (89.1%) of whom were repeat donors, completed the survey at eight blood donation centers. Almost all (98.7%) were aware of HHE, although only half read it in detail, the latter comprising more experienced donors. Most did not hold strong views on deferral, with more than half (59.4%) concurring with both permanent and time‐limited deferral. Seventeen (3.2%) of the sexually active male donors were MSM, of whom six disagreed with permanent deferral while seven agreed with changing to time‐limited deferral. A simpler question structure was preferred by 57% of the respondents for screening MSM to achieve self‐deferral. Conclusions Donors generally do not read through the deferral questionnaire in sufficient detail for making an informed decision. Blood safety would eventually depend on donors' compliance with the deferral mechanism, irrespective of whether it is permanent or time‐limited.